Maternal size in pregnancy and body composition in children. - Gale, C; Javaid, M; Robinson, S; Law, C; Godfrey, K; Cooper, C (2007)
CONTEXT: Evidence suggests that babies' fat mass at birth is greater if their mothers were themselves fatter during pregnancy, but it is unclear whether this association persists into childhood. OBJECTIVE: Our objective was to examine the relation between maternal size in pregnancy, early growth and body composition in children. DESIGN AND SETTING: We conducted a prospective cohort study in Southampton, United Kingdom. PARTICIPANTS: Participants included 216 9-yr-old children whose mothers had participated in a study of nutrition during pregnancy. MAIN OUTCOME MEASURES: Fat mass and lean mass were measured by dual-energy x-ray absorptiometry and adjusted for height (fat mass index and lean mass index). RESULTS: Fat mass index at age 9 yr was greater in children whose mothers had a larger mid-upper arm circumference in late pregnancy or a higher prepregnant body mass index. For 1 sd increase in maternal mid-upper arm circumference in late pregnancy, fat mass index rose by 0.26 [95% confidence interval (CI) 0.06-0.46] sd in boys and by 0.44 (95% CI 0.31-0.57) sd in girls. For 1 sd increase in maternal prepregnant BMI, fat mass index rose by 0.26 (95% CI 0.04-0.48) sd in boys and by 0.42 (95% CI 0.29-0.56) sd in girls. CONCLUSIONS: Mothers with a higher prepregnant body mass index or a larger mid-upper arm circumference during pregnancy tend to have children with greater adiposity at age 9. The extent to which this is attributable to genetic factors, the influence of maternal lifestyle on that of her child, or maternal adiposity acting specifically during pregnancy on the child's fat mass cannot be determined in this study.